On mathematics and mathematicians - Moritz, Robert Édouard, 1868-1940.; Moritz, Cassia K. (New York : Dover Publications, 1958)
"1140 anecdotes, aphorisms, passages by famous mathematicians, scientists, and writers"--front cover
Includes index.
"This new Dover edition first published in 1958 is an unabridged and unaltered republication of the first edition which was originally entitled Memorabilia mathematica or The philomath's quotation-book."--title page verso.
Keywords: Mathematics